Traditional Leaders’ Perspectives on the Risk Factors of Alcohol Abuse Amongst the Youth: The Case of Oshikango in the Ohangwena Region of Namibia - Freeman, Rachel Johanna; Makhubele, Jabulani Calvin; Matlakala , Frans Koketso; Chilwalo, Beatrice Namoonga; Rapholo, Selelo Frank; Ananias, Janetta Agnes; Svinurai , Anesu; Hasheela, Miriam Winnie; Hamuse, Ndanyakuwa Ilonga Tiberia; Mafa , Prudence (Technium Social Sciences Journal, 2022)
Traditional leaders in Oshikango perceive alcohol abuse amongst the youth as one of the greatest challenges of our time. Alcohol abuse amongst the youth is seen as an emergent concern in Namibia, which affects society in terms of high risk behaviours such as crime, violence, absenteeism, and school dropouts. This qualitative study was aimed at exploring and describing traditional leaders’ perspectives on the risk factors of alcohol abuse amongst the youth in Oshikango in the Ohangwena region of Namibia. In this qualitative study, in-depth, face-to-face interviews were conducted with traditional leaders by means of purposive sampling method. An exploratory research design was utilized. Permission to conduct the study was granted by the Ministry of Education, Arts and Culture and ethical approval was obtained from the University of Namibia’s ethical approval committee. Participation was voluntary and based on informed consent. Data were collected with the aid of a semi-structured interview guide. The interviews were transcribed verbatim and field notes were taken. Thematic analysis was used to analyse and interpret the data. The main theme on social determinants revealed that a combination of risk factors, such as excessive alcohol abuse amongst the youth in Oshikango relate to loss of life; stealing; peer delinquents; peer pressure and that parental and familial substance abuse contribute a lack of good role models as well as youth capitalizing on the ignorance of their parents. The study concluded that these social determinants play a significant role in contributing to the risk factors of alcohol abuse amongst the youth in Oshikango. This study therefore recommends that in order to combat alcohol abuse amongst the youth, emphasis should be placed on strategies that address parental and familial alcohol abuse, low parental monitoring, peer norms, peer drinking, peer influence, peer delinquency, programme interventions on how to address these factors at individual, family and society level, as well as law reform and law enforcement.